Delayed Brain Edema and Swelling following Craniectomy for Evacuation of an Epidural Abscess that Improved by Cranioplasty: Case Report - Sugii, Narushi; Matsuda, Masahide; Sekine, Tomokazu; Matsumura, Hideaki; Yamamoto, Tetsuya; Matsumura, Akira (Journal of Neurological Surgery Reports, 2017)
We report a unique case of delayed brain swelling following craniectomy that improved rapidly after cranioplasty, and discuss the potential mechanism underlying this delayed and reversible brain swelling. A 22-year-old woman developed surgical site infection after removal of a convexity meningioma. Magnetic resonance imaging revealed an epidural abscess around the surgical site. Subsequently, the abscess was evacuated, and the bone flap was removed. Later, brain edema around the skull defect emerged and progressed gradually, despite resolution of the infection. The edematous brain developed focal swelling outward through the bone defect without ventricle dilatation. Because we suspected that the edema and swelling were caused by the state of the bone defect, we performed a cranioplasty 10 weeks after the bone flap removal, and brain edema improved rapidly. We hypothesized that the brain edema was initially caused by surgical stress and inflammation, followed by compression of cortical veins between the dural edge and brain tissue, leading to disruption of venous return and exacerbation of brain edema. When delayed focal brain edema and external swelling progress gradually after bone flap removal, after excluding other pathological conditions, cranioplasty should be considered to improve cortical venous congestion caused by postsurgical adhesion.
Keywords: Brain Swelling; bone flap removal; delayed; epidural abscess